Managerial ability, compensation incentives, and corporate performance - Chen, Sidi; Fan, Min; Wang, Xiaohong; Fan, Yaojun; Chen, Sze-Ting; Ren, Shichi (Frontiers in Environmental Science, 2023)
Enterprise managers play a decisive role in the management decisions of enterprises. With the emergence of measurement methods of managerial ability, the influence of managerial ability on enterprise development has been widely concerned. Taking Chinese A-share listed companies from 2007 to 2019 as samples, this paper examines the impact of management capabilities on corporate performance. It is found that managerial ability has a significant positive correlation with the performance of listed companies, and this positive correlation is more obvious when the management has a higher compensation incentive. Further research shows that higher ability management helps to improve the performance of firms with low financing constraints, but has no significant effect on the performance of firms with high financing constraints. In addition, compared with state-owned enterprises, the managerial ability of non-state-owned enterprises can promote the improvement of enterprise performance. This paper studies the impact of managerial ability on firm performance from the perspective of compensation incentives, enriching the related literature on managerial ability and firm performance.